CARB-9, a carbenicillinase encoded in the VCR region of Vibrio cholerae non-O1, non-O139 belongs to a family of cassette-encoded beta-lactamases - Petroni, Alejandro (2004)
Fil: Petroni, Alejandro. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.